2018
DOI: 10.22159/ajpcr.2018.v11i12.28853
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial and Antifungal Activities of Aqueous and Ethanolic Leaf Extracts of Acacia Auriculiformis

Abstract: Objective:The present study focuses on in vitro antimicrobial properties of aqueous and ethanol leaf extract of Acacia auriculiformis tested on Grampositive cocci, Gram-negative bacilli, multidrug-resistant (MDR) Gram-negative bacilli, and fungus.Methods: Ethanol and aqueous extracts of the leaves of A. auriculiformis were prepared. Agar well diffusion was the method for antimicrobial susceptibility. Freshly grown standard strains of Staphylococcus aureus, Enterococcus faecalis, Klebsiella pneumoniae (K. pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These findings suggest that the ethanolic extraction method yielded extracts with broad-spectrum antibacterial activity, effectively targeting a diverse range of bacterial species. Additionally, the data demonstrated significant inhibition of these tested microorganisms by the ethanolic leaf extract (Shobha et al, 2018).…”
Section: Findings and Discussion Antimicrobial Activity Of A Occident...mentioning
confidence: 79%
“…These findings suggest that the ethanolic extraction method yielded extracts with broad-spectrum antibacterial activity, effectively targeting a diverse range of bacterial species. Additionally, the data demonstrated significant inhibition of these tested microorganisms by the ethanolic leaf extract (Shobha et al, 2018).…”
Section: Findings and Discussion Antimicrobial Activity Of A Occident...mentioning
confidence: 79%
“…Several plants offer as a new source of antibacterial, antifungal, and antiviral with significant activity against infective microorganisms [8]. Several studies related to the use of plants as antimicrobial agents have been carried out, such as the antibacterial and antifungal activity of the ethanol extract of Acacia auriculiformis leaves [9] and studies conducted using barks of Casuarina equisetifolia showed antibacterial activity against E. coli with maximum inhibition zone 23±0.24 mm at a 100 μg concentration [10].…”
Section: Resultsmentioning
confidence: 99%
“…The tree contains large amounts of arabinose, rhamnose, galactose, glucuronic acid, and methyl glucuronic acid. 3 The plant has reportedly demonstrated a range of pharmacological properties, including antioxidant & anti-inflammatory 4 , antibacterial & antifungal, 5 antimalarial, 6 antifilarial, 7 cestocidal, 8 antimutagenic & chemopreventive, 9 spermicidal, 10 hepatoprotective, 11 wound-healing, 12 and antidiabetic action. 13 Auriculoside, a flavan glycoside isolated from A. auriculiformis, was found to have central nervous system depressive action.…”
Section: Introductionmentioning
confidence: 99%